The little white bird, or, Adventures in Kensington Gardens / by J.M. Barrie. - Barrie, J. M. (James Matthew), 1860-1937. (Tufts University. Tisch Library., 2016)
1 online resource (iv, 349 pages); Originally published: New York : Charles Scribner's Sons, 1902.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.